Analisis Yuridis terhadap Pengaturan Pengelolaan Tempat Pemrosesan Akhir Berdasarkan Peraturan Daerah tentang Pengelolaan Sampah di Kabupaten Buleleng - Aryabimo Sapta Bagus Putranto; Gede Wirawan; Muhamad Jodi Setianto (Universitas Pendidikan Ganesha, 2026)
Waste management issues are closely linked to efforts to preserve environmental quality. The continued practice of open dumping at Final Processing Sites (TPA) shows that the implementation of an environmentally sound final waste processing system has not been running as it should. This has driven the need to examine the regional legal provisions that serve as the basis for the operation of TPA facilities in Buleleng Regency. This study focuses on the regulation of TPA facilities under Buleleng Regency Regional Regulation Number 1 of 2013 concerning Waste Management, as well as its relationship with national-level legal provisions. The study was conducted using a normative legal research method, using legislation and legal concepts as the basis for analysis. Relevant legal materials were collected through literature review, then analyzed qualitatively to identify the interconnections between legal provisions. The results of the study show that Buleleng Regency Regional Regulation Number 1 of 2013 has positioned final processing as one stage within the overall waste management process, while also placing restrictions on open dumping practices. The substance of this regulation is consistent and in line with Law Number 18 of 2008, Law Number 32 of 2009, and Government Regulation Number 81 of 2012. Therefore, it can be concluded that this regional regulation has provided a legal basis for the operation of TPA facilities directed toward proper waste management and environmental protection.